ALTERNATIF INDEKS GIZI SEIMBANG UNTUK PENILAIAN MUTU GIZI KONSUMSI PANGAN WANITA DEWASA INDONESIA - Perdana, Silvia Mawarti; Hardinsyah, Hardinsyah; Damayanthi, Evy (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to develop a balanced diet index (BDI) in relation to nutritional quality of the diet (NQ) in Indonesian adult females. This study used food consumption data from the Basic Health Research (Riskesdas) of 2010. The food consumption data were collected using 24-h food recall method through a cross-sectional study. Total subject of this study was 61,759 adult females19—55 years. The NQ of 16 nutrients was used as a gold standard in the validity testing. The results showed that the simplest and the most valid measurement was BDI3-60 (correlation coefficients with the NQ=0.7) which was based on three levels of scoring system (0, 5, and 10) and six food groups (carbohydrate food sources, animal protein food, plant protein food, vegetable, fruit, and milk), without considering fat, saturated fat, cholesterol, and sodium. The mean score of BDI3-60 was 31.0±12.1.